A study of electrocardiogram changes in patients with acute stroke - Kumar, Surender; Sharma, Guru Dutt; Dogra, Varan Deep (International Journal of Research in Medical Sciences, 2017)
Background: Electrocardiogram (ECG) changes are observed in patients with acute stroke and may create confusion with ECG changes found in cardiac disorders. The aim of the study was to study the ECG changes in patients with acute stroke who are not suffering from cardiac disorders which are known to show ECG changes. Methods: It was a prospective hospital observational based study conducted for a period of 1 year (20th July 2014 to 20thJuly 2015) including patients with acute stroke. Total 122 patients were enrolled and ECG changes were observed. Results: Various ECG changes are observed (Table 1) in present study including rhythm disturbances (like sinus tachycardia, sinus bradycardia, AF, VPc, RBBB, LBBB, etc.) in 69 patients (56.6%) , bradycardia in 25 patients (19.5%), tachycardia 34 patients (28.1%), prolonged PR interval in 10 patients (9.2%), LAD in 32 patients (26.2%), RAD in 7 patients (5.7%), prolonged QRS interval in 31 patients (25.4%), LVH in 19 patients (15.6%), prolonged QTc interval in 53 patients (43.4%), p wave abnormalities in 30 patients (24.6%), pathological q wave in 11 patients (9.6%), ST segment elevation in 14 patients (11.4%), ST segment depression in 20 patients (16.4%), T wave inversion in 44 patients (36.1%) and presence of U wave in 9 patients (7.1%). Conclusions: QTc prolongation followed by T-wave inversion followed by ST segment changes were the most frequent ECG changes observed in patients with acute stroke. Various types of arrhythmias like sinus tachycardia, sinus bradycardia, AF, VPCs, BBB, Heart blocks, etc. were also among the common ECG findings. Furthermore ECG findings like PR interval prolongation, QRS interval prolongation and P-wave abnormalities (hardly any study is there in literature about these ECG findings) were additional findings in this study.